(untitled) (Experimental biology, 2020)
The study of the polymorphism of folate cycle genes MTR, MTRR, MTHFR in women of the Kazakh ethnic group with complications of pregnancy (risk group, 196 pregnant women) and with the standard physiological course of pregnancy (control, 198 pregnant women) was carried out. In women at risk, the first two pregnancies ended up with spontaneous miscarriages, a pre-eclampsia, eclampsia, fetal loss syndrome, and other obstetric complications which were reported in the anamnesis. In the control group, the first two or more pregnancies completed with normal child birth; there was no history of pregnancy complications recorded in the anamnesis. The study was conducted by the case-control method. DNA isolated from venous blood leukocytes was used for PCR analysis in RealTime mode using allele-specific primers indicating gene polymorphism. A statistical analysis of the association of genetic polymorphisms was fulfilled using Software GraphPad Instat ™ Software (V. 2.04. Ralf Stahlman, Purdue University) and standard techniques. To determine the association of alleles and genotypes with pregnancy complications using the odds ratio indicator (OR, 95% CI), 4 types of inheritance models (multiplicative, total, dominant and recessive) were considered. The analysis of the association of various gene combinations of the folate cycle genes with pathology was applied. The data obtained for the frequency of occurrence of polymorphic variants of the folate cycle genes in pregnant women at risk and in the control group did not reveal statistically significant differences across all inheritance models. Also, no statistically significant differences were determined between the examined groups when analyzing the association of various variants of the studied genes with pregnancy complications. The data suggest that polymorphism of folate cycle genes does not play a significant part in the formation of the pregnancy complications in women of the Kazakh ethnic group. Keywords: pregnancy complications, folate cycle genes, gene polymorphism.